Assessment of Global and Network Models of Devolatilization for Numerical Analysis of Pulverized Coal Combustion - YILMAZ, BARIŞ (TAYLOR & FRANCIS INC, 2019)
Mathematical modeling of devolatilization plays a significant role in the prediction of flame development in solid fuel combustion simulations. Commonly implemented devolatilization models available in the literature to simulate pulverized coal combustion are reviewed and evaluated. The effect of the particle heating rate on the onset of devolatilization and on final volatile yield is discussed. Selected devolatilization models are investigated with respect to their implementation in Computational Fluid dynamics (CFD) simulations of methane-assisted pulverized coal jet flame experiments. Differences in volatile release region, particle temperature and species concentration are presented and discussed with comparisons to the experimental data.
Keywords: Pulverized coal combustion; devolatilization models; pyrolysis; CFD modeling; KINETICS; HEAT